Young John Quincy - Harness, Cheryl (Bradbury Press ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1994)
Presents the events leading up to the Declaration of Independence as seen through the eyes of the boy who would grow up to be the sixth president of the United States.